Defining the Role of Sport and Exercise Physicians: The Experience of Different Referrer Types in New Zealand - Aubrey, Brendon; Fulcher, Mark L; Reid, Duncan (BMJ, 2024)
The aim of this study was to analyse the reasons health professionals refer to sport and exercise physicians (SEPs) and to define what service gap the specialty fills. This was a qualitative study design using thematic analysis. Online focus group interviews consisting of 4–6 participants in each group were conducted separately with physiotherapists, emergency clinicians, general practitioners and orthopaedic surgeons practising in New Zealand. Thematic analysis of the focus group interviews was then used for the identification of common themes around referral tendencies towards SEPs. Three primary themes were identified relating to referrals towards SEPs: (1) role utilisation of SEPs, (2) collaboration and (3) accessibility. SEPs are viewed as experts in the assessment, investigation and diagnosis of musculoskeletal (MSK) conditions, including some which might traditionally be viewed as surgical diagnoses. Some confusion or lack of understanding exists regarding the range of conditions that SEPs can treat and manage, with some referrers assuming that SEPs only treat sport-related injuries. SEPs are often used alongside other specialist practitioners in the management of patients with MSK conditions. This requires collaboration with other health professionals who also treat MSK conditions to ensure the best patient outcome. A common feeling towards SEPs is they are easily accessible compared with other potential health providers who may also treat MSK conditions such as orthopaedic surgeons and general practitioners, and that SEPs provide sound management plans and access to investigations such as MRI, in a timely fashion.
Keywords: 1106 Human Movement and Sports Sciences; 3202 Clinical sciences; 4207 Sports science and exercise